To construct the norm of hand hygiene behavior scale for medical staff in tertiary general hospitals in China - Tao, Juan; Liu, Shuang-yan; Tang, Si-ping; Yu, Ye; Xiang, Sheng-yu (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to construct a national norm for the Chinese version of the Hand Hygiene Behavior Questionnaire (HHBQ-C) among medical staff in tertiary general hospitals in China and to provide a basis for assessing the current status and influencing factors of hand hygiene practices among medical staff.MethodsUsing a stratified random sampling method, a total of 3,000 medical staff from 12 provinces across three regions of China, eastern, central, and western, were selected as research subjects between April 2023 and June 2023. Each region included four provinces. The General Information Questionnaire and the HHBQ-C were used to evaluate the medical staff. Norms for means, percentiles, demarcation, and classification were established.ResultsA total of 2,793 medical staff were included in this study. Gender and age were used to establish the mean norms of the HHBQ-C. Based on the results of the single-factor analysis, classification norms were established by selecting the characteristics that showed significant differences, namely age, occupation, work pressure, and workload. Percentile norms were established at 5% intervals. The scores on the HHBQ-C were divided into four grades: low, medium, high, and very high.ConclusionThe established national norms for the HHBQ-C in tertiary hospitals provide a solid basis for evaluating influencing factors and guiding targeted interventions to improve hand hygiene compliance and reduce HCAIs.